Lyydiläiskysymys : Kansa vai heimo, kieli vai murre? - Pahomov, Miikul (Helsingin yliopisto, 2017)
Researchers of the Finnic languages have presented various views on the position of Ludian. It has been regarded as an independent language by some and a dialect of Karelian (or Vepsian) by others. Researchers have also pondered whether the Ludians are their own people or a Karelian (or Vepsian) tribe. The goal of this research is to define the historical and taxonomical position of the language variety spoken by the Ludian people. This study is the first comprehensive examination of the history of Ludian and its speakers. The primary research method is the historical-comparative method, supplemented where applicable with language sociology. The historical investigation is mainly based on written sources, while the linguistic analysis is based on material collected by the author in Kuujärvi, in comparison with other available material. The focus is on the structural features of the language. Today, Ludian is one of the most endangered Finnic languages, with at most 300 speakers. Material is not available for all dialects spoken at the start of the 20th century, as those spoken beyond the eastern border of the area were extinct by the 1940s. The number of Ludian speakers at the start of the 20th century can be estimated at 15,000 - 20,000. Ludians self-identification differs from the official classifications used in Russia. An analysis of Kuujärvi Ludian reveals that it shares features with other Ludian dialects, but also with Karelian-Olonets and Vepsian. Classifying Ludian as a Karelian dialect is problematic, as it is difficult to pinpoint any features shared by both Ludian and Karelian-Olonets but not by Vepsian. Nor can Vepsian be viewed as a substrate of Ludian and Olonets due to its phonological properties. Compared to Vepsian, Ludian contains more evidence of the ancient language from which Ludian, Olonets and Vepsian are presumed to originate. Based on the many similarities between Ludian and Olonets, it can be ascertained that, for example, Southeast Olonets, and developed based on Kuujärvi Ludian. The ...